Project: automaton - Lau, Shan Yu (Nanyang Technological University, 2022)
The purpose of this project was to crate an interactive 3D game demo with an emphasis on asset creation. I used a variety of 3D software as well as Unreal Engine to produce the demo. The scope had to be cut down significantly to meet the deadlines of the project at the level of detail intended for the project.